Specification, transferability and the effect of data outliers in modelling the choice of mode in urban travel. - Talvitie, Antti; Kirshner, Daniel (My University, 1978)
Three problems of great importance to urban travel demand modeling using multinominal logit models are examined in this paper. They are (1) the effect of data outliers on model coefficients; (2) the effect of model specification on coefficients and model explanatory power; and (3) the transferability of model coefficients within the region, between regions, and in time. Four data sets are used in the study. They are Washington, D. C., Minneapolis-St. Paul, and two data sets from the San Francisco Bay Area, Pre-BART and Post-BART. The data are standard home-interview survey data appended with network supplied modal travel cost and time information. The findings of the research are occasionally contradictory; the majority of the evidence supports the following conclusions. The ,,outliers'' do not have a statistically significant effect (at 0.05 level) on the coefficients; however, the outliers can have a substantial effect on the point estimates of the coefficients. Model specification has an impact on model coefficients and model explanatory power. In particular, the definition of out-of-vehicle travel time appears to be important and, if available, the use of separate walk and wait times is prefered over their sum, the out-of-vehicle time. Finally, the model coefficients do not appear transferable within region, between regions, or in time.
Keywords: Verkehrstheorie; Modell; Stadtverkehr